Meteorin-like alleviates hepatic steatosis by regulating hepatic triglyceride secretion and fatty acid oxidation - Lingyu Song; Yali Huang; Lu Liu; Xuebing Chang; Laying Hu; Guifang Wang; Lifen Xu; Tian Zhang; Yuanyuan Wang; Ying Xiao; Hong Yang; Suye Ran; et al. (Cell Reports)
Summary: Amid a rising prevalence of non-alcoholic fatty liver disease (NAFLD), there is still an unmet need to better treat it. We identified a secreted factor, Meteorin-like (Metrnl), with decreased levels in livers with hepatic steatosis. Notably, recombinant Metrnl ameliorated hepatic steatosis in NAFLD mouse models. Mechanistically, Metrnl exerted dual effects by promoting triglyceride (TG) transportation by the phosphatidylinositol 3-kinase (PI3K)/Akt/Sp1/cytidylyltransferase α (CCTα) axis, thereby increasing the biosynthesis of phosphatidylcholine (PC) to facilitate TG secretion from the liver while facilitating AMP-activated protein kinase (AMPK)-dependent fatty acid oxidation (FAO). Exogenous injection of cytidine diphosphocholine (CDP)-choline, the production of CCTα, to increase PC synthesis, was shown to restore the inhibition of TG secretion in hepatic Metrnl-deficient (LKO-Met) mice. Combining CDP-choline and an AMPK activator was sufficient to rescue hepatic steatosis in LKO-Met mice. Collectively, these findings reveal unexpected roles of Metrnl as a factor in PC biosynthesis, TG secretion, and FAO, suggesting potential therapeutic application for NAFLD.